Lipid Metabolism Was Associated With Oocyte in vitro Maturation in Women With Polycystic Ovarian Syndrome Undergoing Unstimulated Natural Cycle - Liu, Tao; Liu, Dongming; Song, Xueling; Qu, Jiangxue; Zheng, Xiaoying; Li, Jia; Yang, Rui; Yang, Shuo; Zhang, Xi; Wang, Haiyan; Yan, Liying; Ma, Caihong; et al. (Frontiers in Cell and Developmental Biology, 2021)
Objective: Hyperlipidemia are common polycystic ovarian syndrome (PCOS)-related metabolic dysfunctions and can adversely affect assisted reproductive technology (ART) outcomes in controlled ovarian hyperstimulation (COH) cycles. The objective of this study is to analyze the relationship between lipid metabolism and ART outcomes in unstimulated natural cycles without the utilization of ovarian induction drugs, which is still uncertain. Methods: This retrospective study included infertile women with PCOS between 21 to 40 years old undergoing unstimulated natural cycles from January 1, 2006 to December 31, 2019. Lipid metabolism was measured by body mass index (BMI) and serum biochemical parameters including total cholesterol (TC), triglycerides (TG), high and low density lipoprotein cholesterol (HDL-C, LDL-C). ART outcomes were measured by number of oocytes retrieved, oocyte maturation quality and developmental potential, clinical pregnancy and live birth. Results: A total of 586 patients were included in this study. Multivariate Possion logliner analysis showed that high TC (≥5.18 mmol/L), triglycerides (TG) (≥1.76 mmol/L), LDL-C (≥3.37 mmol/L) levels and low HDL-C levels (≤1.04 mmol/L) were significantly (PTC= 0.001, PTG< 0.001, PHDL-C< 0.001, PLDL-C< 0.001) associated with increased number of oocytes retrieved. BMI was significantly negatively associated with maturation rate (P< 0.001), fertilization rate (P< 0.001) and transferrable embryo rate (P= 0.002). High TG levels and low HDL-C levels were also associated with decreased maturation rate (PTG< 0.001, PHDL-C= 0.026). Logistic regression analysis showed statistically significant association between obesity (≥28.0 kg/m2) and decreased live birth rate (P= 0.004) as well as cumulative live birth rate (P= 0.007). Conclusion: This is the first study that focused on the relationship between basal lipid metabolism and ART outcomes in women with PCOS undergoing unstimulated natural cycles. The results showed that high levels of lipid metabolic parameters were associated with increased number of oocytes retrieved and obesity was closely associated with impaired oocyte maturation quality and developmental potential as well as poor live birth outcomes.